Passively mode-locking operation fiber laser generation using black phosphorus saturable absorber at 1-micron wavelength region / Ahmad Haziq Aiman Rosol ...[et al.] - Rosol, Ahmad Haziq Aiman; Abdul Rahman, Husna; Jusoh, Zulzilawati; Abdul Latiff, Anas; Mohd Rusdi, Muhammad Farid; Harun, Sulaiman Wadi (UiTM Press, 2017)
We demonstrate the generation of mode-locked ytterbium-doped fiber laser (YDFL) by using a black phosphorus (BP) as a passively saturable absorber (SA). The BP SA is exfoliated from the commercial bulk crystal BP by using a standard scotch tape. To realize the mode-locking operation, a piece of BP tape is adhered onto a fiber ferrule tip by an assistant of index matching gel before being sandwiched. Under 270 mW to 490 mW, the stable repetition rate of 14.85 MHz obtains at 1100 nm wavelength with maximum pulse energy of 0.94 nJ. Our findings may contribute to the pathway of graphene-like materials specifically for ultrafast fiber laser generation application.